Analysis of Viral Load Values in PLHIV Receiving Peer Support During Six Months of Treatment - Tahir, Muh. Yusuf; Taslim, Muh.; Wardani, Deni (Malikussaleh University, Aceh, Indonesia, 2025)
HIV/AIDS remains one of the significant global health challenges that require long-term management for viral suppression. Antiretroviral therapy is considered the cornerstone of treatment. However, while ART has proved effective, there is limited data regarding the effectiveness of peer support on viral load outcomes. The paper, therefore, seeks to describe changes in viral load among PLHIV who received peer support over six months. We used a descriptive quantitative approach in this study; the data source was obtained from secondary data by the Ministry of Health through its SITRUS system and monitoring ART treatment in PLHIV patients. A total of 58 participants with ART treatment in health facilities with PSS were used in this study. Data were collected from several healthcare facilities and then analyzed descriptively to review the distribution of changes in viral loading within six months of treatment. Results showed that the success of viral suppression varied depending on the kind of ART treatment. However, the viral load values were lower across the board due to peer support. Therefore, peer support influenced adherence to therapy by participants irrespective of individual personalities and personal traits. Despite various treatment response rates, the general trend of the findings in this study was that peer support contributed to PLHIV's adherence to their regimes. This can be interpreted into generally better health conditions, including less viral load as a critical attribute essential for low levels of HIV transmission and the procreation of slow-onset diseases. These findings emphasize how important peer support is to increase ART adherence and viral suppression, which is key in the control of HIV according to public health strategies.